Pharmacology in translation: the preclinical and early clinical profile of the novel α2/3 functionally selective GABAA receptor positive allosteric modulator PF‐06372865. (18th January 2018) - Nickolls, Sarah A; Gurrell, Rachel; van Amerongen, Guido; Kammonen, Juha; Cao, Lishuang; Brown, Adam R; Stead, Clara; Mead, Andy; Watson, Christine; Hsu, Cathleen; Owen, Robert M; Pike, Andy; et al.
Abstract : Background and Purpose: Benzodiazepines, non‐selective positive allosteric modulators (PAMs) of GABAA receptors, have significant side effects that limit their clinical utility. As many of these side effects are mediated by the α1 subunit, there has been a concerted effort to develop α2/3 subtype‐selective PAMs. Experimental Approach: In vitro screening assays were used to identify molecules with functional selectivity for receptors containing α2/3 subunits over those containing α1 subunits. In vivo receptor occupancy (RO) was conducted, prior to confirmation of in vivo α2/3 and α1 pharmacology through quantitative EEG (qEEG) beta frequency and zolpidem drug discrimination in rats respectively. PF‐06372865 was then progressed to Phase 1 clinical trials. Key Results: PF‐06372865 exhibited functional selectivity for those receptors containing α2/3/5 subunits, with significant positive allosteric modulation (90–140%) but negligible activity (≤20%) at GABAA receptors containing α1 subunits. PF‐06372865 exhibited concentration‐dependent occupancy of GABAA receptors in preclinical species. There was an occupancy‐dependent increase in qEEG beta frequency and no generalization to a GABAA α1 cue in the drug‐discrimination assay, clearly demonstrating the lack of modulation at the GABAA receptors containing an α1 subtype. In a Phase 1 single ascending dose study in healthy volunteers, evaluation of the pharmacodynamics of PF‐06372865 demonstrated a robust increase in saccadic peak velocity (a marker of α2/3 pharmacology), increases in beta frequency qEEG and a slight saturating increase in body sway. Conclusions and Implications: PF‐06372865 has a unique clinical pharmacology profile and a highly predictive translational data package from preclinical species to the clinical setting.